INTEREST GROUP SESSION - HEALTH BEHAVIOR CHANGE: THE ANNUAL WELLNESS VISIT: IMPLEMENTATION IN REAL WORLD SETTINGS AND ASSOCIATED FINDINGS. (11th November 2018) - Resnick, B; SheinfeldGorin, S
Abstract: The Medicare Annual Wellness Visit (AWV) was introduced in 2011 as part of the Medicare Part B expansion under the Affordable Care Act. The AWV was promoted to encourage preventive care and mitigate health risks in aging patients through required age- appropriate and risk modifying screenings and assessments. It does not include a comprehensive physical exam. Rather it incorporates vital signs such as height, weight and blood pressure, assessments of cognition, mood, current immunization status, cancer screenings, and advanced directives. Unfortunately, the implementation of the AWV has been relatively low nationally; further, little is known about the benefits of the AWV from a patient quality of life perspective, impact on health status or cost benefits. While the AWV provides a critical opportunity to reduce risks for diabetes and hyperlipidemia, for example, through physical activity and dietary counseling, and the detection of cancer, there is insufficient provider team assessment and followup to facilitate either near-or longer-term behavior change. Moreover, little is being done to apply the findings from the AWV to facilitate behavior change through physical activity and dietary counseling, to follow-up on positive findings from cancer screening, or to reduce falls. The purposes of this symposium are to: provide a comprehensive review of the AWV; describe implementation of the AWV in a real-life setting; summarize AWV cognitive assessments; address the cost implications of the AWV; and discuss health disparities with regard to the AWV and opportunities for implementing behavior change through the AWV across a broad range of older adults.